2020
DOI: 10.1001/jama.2020.6928
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Glucose Monitoring on Hypoglycemia in Older Adults With Type 1 Diabetes

Abstract: for the Wireless Innovation for Seniors With Diabetes Mellitus (WISDM) Study Group IMPORTANCE Continuous glucose monitoring (CGM) provides real-time assessment of glucose levels and may be beneficial in reducing hypoglycemia in older adults with type 1 diabetes. OBJECTIVE To determine whether CGM is effective in reducing hypoglycemia compared with standard blood glucose monitoring (BGM) in older adults with type 1 diabetes. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted at 22 endocrinolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
183
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 29 publications
9
183
0
5
Order By: Relevance
“…S everal studies have shown use of continuous glucose monitors (CGMs) can improve glycemic control and reduce hypoglycemia for participants with type 1 diabetes (T1D). [1][2][3] The DIAMOND T1D trial found that participants randomized to receive a real-time continuous glucose monitor (rtCGM) had a 0.6% greater reduction in mean hemoglobin A1c (HbA1c) and spent an additional 77 min per day in range 70-180 mg/dL compared with participants in selfmonitoring of blood glucose (SMBG) group. 4 Beyond the finding of a clinically relevant overall benefit of rtCGMs, it is important to assess improvement at an individual level to identify individuals who can potentially benefit the most from rtCGM use.…”
Section: Introductionmentioning
confidence: 99%
“…S everal studies have shown use of continuous glucose monitors (CGMs) can improve glycemic control and reduce hypoglycemia for participants with type 1 diabetes (T1D). [1][2][3] The DIAMOND T1D trial found that participants randomized to receive a real-time continuous glucose monitor (rtCGM) had a 0.6% greater reduction in mean hemoglobin A1c (HbA1c) and spent an additional 77 min per day in range 70-180 mg/dL compared with participants in selfmonitoring of blood glucose (SMBG) group. 4 Beyond the finding of a clinically relevant overall benefit of rtCGMs, it is important to assess improvement at an individual level to identify individuals who can potentially benefit the most from rtCGM use.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JAMA, 2 clinical trials provide important data on the efficacy of CGM in these high-risk populations with type 1 diabetes. 5,6 The periods of adolescence and young adulthood (13-24 y) are distinctive developmental stages marked by transition of disease self-management tasks from family to self in the midst of tumultuous change in an individual's social, geographic, financial, and health care situations. 7 As a result, adolescents and young adults exhibit the highest hemoglobin A 1c (HbA 1c ) levels and rates of hospitalization of all age groups with type 1 diabetes.…”
mentioning
confidence: 99%
“…12,13 Older populations are more prone than younger populations to severe hypoglycemic episodes, which in turn contribute to dementia, risk of falls, glycemic variability, and mortality. 14 To study whether CGM could reduce hypoglycemia incidence, Pratley and colleagues 6 performed a randomized clinical trial that compared the effect of CGM (n = 103) with BGM (n = 100) in older adults (median age, 68 years) with type 1 diabetes in 22 diabetes centers across the US. The primary outcome was reduction in hypoglycemia (glucose <70 mg/dL) over 6 months.…”
mentioning
confidence: 99%
“…1 Several decades were required to evolve from urine glucose monitoring to self-monitoring of blood glucose. 2 Despite ample evidence demonstrating the efficacy of a continuous glucose monitor (CGM) in improving glycemic control and safety in hypoglycemia reduction in patients with insulin-requiring diabetes, [3][4][5][6][7][8] it required nearly two decades to replace glucose meters (that too on a limited basis). 9 Usually it requires a decade to adopt new changes in the clinical practice, commonly known as the ''research to practice gap.''…”
Section: Introductionmentioning
confidence: 99%